Problems of introduction of automated external defibrillators for application in Ukraine. Defibrillator is one of the most advanced radio electronic medical devices allowing considerable reduction of deaths caused by ventricular defibrillation - Kostiv, Myron (Видавництво Львівської політехніки, 2010)
In this paper problems of introduction of automated external defibrillators for application in Ukraine are considered by the author.
Keywords: AED; cardiac defibrillator; fibrillation; bipolar pulse